No shame, no fear - Turnbull, Ann. (London : Walker Books, 2012)
In England in 1662, a time of religious persecution, fifteen-year-old Susanna, a poor country girl and a Quaker, and seventeen-year-old William, a wealthy Anglican, meet and fall in love against all odds.
Young Adult.
Young Adult
Keywords: Persecution -- Juvenile fiction; Quakers -- Juvenile fiction; Social classes -- Juvenile fiction; Historical fiction; Persecution -- Fiction; Quakers -- Fiction; Social classes -- Fiction; Historical fiction; Persecution -- Fiction; Social classes -- Fiction; Society of Friends -- Fiction; Great Britain -- History -- Charles II, 1660-1685 -- Juvenile fiction; Great Britain -- History -- Charles II, 1660-1685 -- Fiction; Great Britain -- History -- 1603-1714, Stuarts -- Fiction